2017
DOI: 10.1007/s11010-017-3101-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytoglobin inhibits migration through PI3K/AKT/mTOR pathway in fibroblast cells

Abstract: Cell proliferation and migration are crucial in many physiological processes including development, cancer, tissue repair, and wound healing. Cell migration is regulated by several signaling molecules. Identification of genes related to cell migration is required to understand molecular mechanism of non-healing chronic wounds which is a major concern in clinics. In the current study, the role of cytoglobin (CYGB) gene in fıbroblast cell migration and proliferation was described. L929 mouse fibroblast cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…As a member of the hexacoordinate globin superfamily, CYGB was shown to protect cells against hypoxic stress [15, 33], and inhibit the PI3K/AKT/mTOR pathway [34]. However, how CYGB suppresses tumor growth remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the hexacoordinate globin superfamily, CYGB was shown to protect cells against hypoxic stress [15, 33], and inhibit the PI3K/AKT/mTOR pathway [34]. However, how CYGB suppresses tumor growth remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…CFU assay was performed to determine whether compound 5a affects the colony‐forming ability of cells as described previously (Demirci et al., ). Briefly, PC‐3, DU145 and LNCaP cells were seeded at a cell density of 100 cell per well of six‐well plates in the presence of respective IC 50 concentrations of compound 5a for each cell line.…”
Section: Methodsmentioning
confidence: 99%
“…Cygb is significantly deregulated by its promoter hypermethylation in most malignancies, 26,28,29 thereby promoting tumorigenesis and progression. [16][17][18][19][20][21][30][31][32] In this study, we found that Cygb is significantly deregulated in human HCC tissues, as compared with these adjacent non-tumor tissues and hepatolithiasis tissues ( Figure 1A-C), Cygb decrease promotes HCC proliferation, whereas Cygb restoration inhibits cell proliferation (Figure 2A-D). We proposed that Cytoglobin functions as tumor suppressor, and its decrease is negatively associated with HCC progression.…”
Section: Discussionmentioning
confidence: 64%